2019
DOI: 10.1007/s00216-019-01948-2
|View full text |Cite
|
Sign up to set email alerts
|

The application of a lateral flow immunographic assay to rapidly test for dexamethasone in commercial facial masks

Abstract: Dexamethasone (DE) is a synthetic glucocorticoid that is frequently added to cosmetic products for its good short-term effects, especially in facial masks, but long-term use is hazardous to the health. The abuse of DE in whitening and acne cosmetic products is currently a serious problem in China. It is necessary to establish a rapid method of detecting illegal DE addition in cosmetics. In the present study, a monoclonal antibody (mAb) against DE, 2D5-3D12, was developed that displayed cross-reactivities of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We used the VISIA system to evaluate the deep blood vessels of rosacea by assessing the confluent and diffuse background erythema, and found that the severity of the background erythema and cheek involvement were supportive evidence for rosacea diagnosis. Telangiectasis is another important presentation of rosacea under VISIA, which can often be observed in control subjects with sun-damaged facial skin (such as photoaging) or glucocorticosteroid-induced dermatitis ( Helfrich et al, 2015 ; Lahiri & Coondoo, 2016 ; Wang et al, 2019 ). However, the telangiectasis displayed by VISIA for rosacea were preferably located in the upper eyelid ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used the VISIA system to evaluate the deep blood vessels of rosacea by assessing the confluent and diffuse background erythema, and found that the severity of the background erythema and cheek involvement were supportive evidence for rosacea diagnosis. Telangiectasis is another important presentation of rosacea under VISIA, which can often be observed in control subjects with sun-damaged facial skin (such as photoaging) or glucocorticosteroid-induced dermatitis ( Helfrich et al, 2015 ; Lahiri & Coondoo, 2016 ; Wang et al, 2019 ). However, the telangiectasis displayed by VISIA for rosacea were preferably located in the upper eyelid ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Food and Drug Administration website of China, from 2016 to 2018, glucocorticoids were illegally added to many batches of cosmetic products. Notably, the abuse of glucocorticoid was particularly prevalent in facial masks and beauty salon products for short-term commercial effects [37,38]. It has well accepted that dilation of blood vessels, red spots, and thinning of the facial skin like the feature of ETR would take place in the process of long-term use of glucocorticoid [38].…”
Section: Plos Onementioning
confidence: 99%
“…Notably, the abuse of glucocorticoid was particularly prevalent in facial masks and beauty salon products for short-term commercial effects [37,38]. It has well accepted that dilation of blood vessels, red spots, and thinning of the facial skin like the feature of ETR would take place in the process of long-term use of glucocorticoid [38]. Therefore, if the source and the contents of skin care products are unreliable, the more frequent and more regular skin care people do, the more likely they will suffer skin barrier damage and even attack steroid-induced rosacea.…”
Section: Plos Onementioning
confidence: 99%
“…Due to the ease of use and commercial attractiveness of immunochromatographic assays [ 11 ], research and development in this area has expanded considerably. A wide range of analytes including viruses (e.g., hepatitis B [ 12 ], HIV [ 13 ], SARS-CoV-2 [ 14 ]), bacteria (e.g., Helicobacter pylori [ 15 ], Staphylococcus aureus [ 16 ], Salmonella [ 17 ]), toxins [ 18 , 19 , 20 ], pesticides [ 21 ], cancer markers [ 22 , 23 ], antibiotics [ 24 , 25 ], drugs [ 26 , 27 ], terpenes [ 28 ] and steroids [ 29 , 30 , 31 , 32 , 33 ] have been used to construct useful immunochromatographic assays.…”
Section: Introductionmentioning
confidence: 99%